PENGARUH CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINE SHOP (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MULAWARMAN) - ARINDA ZEN TIFFANY; SYARIFAH HUDAYAH; SAIDA ZAINUROSSALAMIA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
Influence Buying Decision Against Celebrity Endorser Onlineshop Products (a case study in the Faculty of Economics and Business, University of Mulawarman). The purpose of this study was to determine whether the celebrity endorser influence the purchasing decisions of products to be purchased by the consumer in account social.From these results, it is known from multiple linear regression equation Y = 0.272 + 0.237 + 0.265 + 0.240 + 0.251 with a total value is positive, the variables X1 , X2 , X3 and X4 influential Y. That visibility , credibility , power and attraction celebrity endorser influence on purchase decisions onlineshop product. Keywords: Celebrity Endorser, Onlineshop.